2013
DOI: 10.1186/1471-2407-13-447
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of clinicopathologic and operative factors on short-term and long-term survival in renal cell carcinoma with venous tumor thrombus extension: a multi-institutional retrospective study in Japan

Abstract: BackgroundAlthough the percentage of patients with renal cell carcinoma (RCC) extending into venous systems is unexpectedly high, the prognostic impact and independency of venous tumor thrombus-related factors on overall survival (OS) remain controversial. Furthermore, the prognostic impact of various clinicopathologic factors including tumor thrombus-related factors on OS may change with elapsed years after the intervention and also with follow-up duration of participants. The aim of the study is to explore i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 28 publications
1
28
1
Order By: Relevance
“…In the present study, the 1-, 3-, and 5-year CSS rates were 93.0%, 70.9%, and 58.1%, respectively, in all these patients, and were 95.3%, 82.6%, and 68.6%, respectively, in those without metastasis on diagnosis of the cancer. These figures were better than those reported previously [ 3 , 9 , 20 ]. Such differences may arise from the fact that more patients with renal venous tumor thrombus only were included in our study, and the proportion of patients who underwent surgery within the past 3 years was relatively high in the present study.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…In the present study, the 1-, 3-, and 5-year CSS rates were 93.0%, 70.9%, and 58.1%, respectively, in all these patients, and were 95.3%, 82.6%, and 68.6%, respectively, in those without metastasis on diagnosis of the cancer. These figures were better than those reported previously [ 3 , 9 , 20 ]. Such differences may arise from the fact that more patients with renal venous tumor thrombus only were included in our study, and the proportion of patients who underwent surgery within the past 3 years was relatively high in the present study.…”
Section: Discussioncontrasting
confidence: 78%
“…Perinephric fat invasion usually suggests a greater invasiveness of tumor. Although some studies have not shown perinephric fat invasion to be an independent prognostic predictor [ 9 , 22 ], two multicenter, large-scale studies have demonstrated that perinephric fat invasion correlated significantly with a poor prognosis and was an independent prognostic predictor for CSS in all patients [ 6 , 25 ]. The present study suggested perinephric fat invasion to be an independent prognostic predictor in Chinese patients with RCC and VTT but without metastasis; however, perinephric fat invasion was a statistically significant predictor for CSS of all patients in univariate but not in multivariate analysis (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some international groups have performed RCC studies based on multi-institutional RCC DBs. Examples include the renal mass study of CROES (Clinical Research Office of the Endourological Society) [ 3 4 ], CORONA (Collaborative Research On Renal Neoplasms Association) Project [ 5 6 7 8 9 ], SATURN (Surveillance and Treatment Update Renal Neoplasms) Projects [ 8 9 ] and Japanese multicenter studies [ 10 11 ], which have reported high-quality research results. Some multi-institutional retrospective studies on RCC have also been conducted in Korea [ 12 13 14 ], but there have been no large DB systems to collect data on Korean RCC.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to remove the vascular wall infiltrated by IVCTT. However, IVC infiltrated by IVCTT is a risk factor for poor prognosis [ 23 ] and an important factor for IVC resection. Thus, a comprehensive preoperative imaging evaluation may allow surgical urologists to more effectively treat the IVC [ 19 , 21 ].…”
Section: Discussionmentioning
confidence: 99%